Even moderate liver fat accumulation below conventional fatty liver cutoffs is linked to multiple metabolomic alterations and gestational dysglycemia in Asian women of reproductive age - Priti Mishra; Suresh Anand Sadananthan; Jadegoud Yaligar; Kok Hian Tan; Yap Seng Chong; Peter D. Gluckman; Keith M. Godfrey; Marielle V. Fortier; Johan G. Eriksson; Jerry Kok Yen Chan; Shiao-Yng Chan; Dennis Wang; et al. (BMC Medicine)
Abstract Background It is not clear if conventional liver fat cutoff of 5.56% weight which has been used for identifying fatty liver in western populations is also applicable for Asians. In Asian women of reproductive age, we evaluate the optimum metabolic syndrome (MetS)-linked liver fat cutoff, the specific metabolomic alterations apparent at this cutoff, as well as prospective associations of preconception liver fat levels with gestational dysglycemia. Methods Liver fat (measured by magnetic resonance spectroscopy), MetS, and nuclear magnetic resonance (NMR)-based plasma metabolomic profiles were assessed in 382 Asian women, who were planning to conceive. Ninety-eight women went on to become pregnant and received an oral glucose tolerance test at week 26 of gestation. Results The optimum liver fat cutoff for diagnosing MetS was 2.07%weight. Preconception liver fat was categorized into Low (liver fat < 2.07%), Moderate (2.07% ≤ liver fat < 5.56%), and High (liver fat ≥ 5.56%) groups. Individual MetS traits showed worsening trends, going from Low to Moderate to High groups. Multiple plasma metabolomic alterations, previously linked to incident type 2 diabetes (T2D), were already evident in the Moderate group (adjusted for ethnicity, age, parity, educational attainment, and BMI). Both a cross-sectional multi-metabolite score for incident T2D and mid-gestational glucose area under the curve showed increasing trends, going from Low to Moderate to High groups (p < 0.001 for both). Gestational diabetes incidence was 2-fold (p = 0.23) and 7-fold (p < 0.001) higher in the Moderate and High groups relative to the Low group. Conclusions In Asian women of reproductive age, moderate liver fat accumulation below the conventional fatty liver cutoff was not metabolically benign and was linked to gestational dysglycemia. The newly derived cutoff can aid in screening individuals before adverse metabolic phenotypes have consolidated, which provides a longer window for preventive strategies.